Anaysis of composite beams in bending - Li, Yu Fu (2016)
This project involves the study of the effects of coupling in laminated beam subjected to bending. To carry out the experimental test and data analysis, the CFRP manufacturing process has been investigated and practised. Four laminate orientations of antisymmetric cross-ply and angle-ply were tested. They were [0_4^°/〖90〗_4^°], [〖90〗_4^°/0_4^°], [〖+45〗_4^°/〖-45〗_4^°] and [〖-45〗_4^°/〖+45〗_4^°]. The laminate CFRP was cut using the diamond cutter to a dimension of 14mm by1.4mm. The span of the laminated beam was varied at 80mm, 100mm and 120mm. Fully clamped beam bending test was conducted at a feed rate of 3mm/minute using the Intron-5569 machine. To ensure that the tests conducted are reliable and repeatable, a total 48 specimens were tested. All tests were video recorded to capture the deformation process and failure mode. By checking the Load versus Center deflection graphs, 9 out of 48 specimens were qualified for analysis. Subsequently, bending stiffness was calculated for each orientation. The membrane deformation, ɛ_x^o and ɛ_y^o, caused by bending moment and the out of plane curvature, k_x and k_y, has been computed. The failure pattern was categorised based on the laminate orientation. The relationship between the different laminate orientation with the same span was studied. The source of errors during the test and recommendations for the experimental test were discussed for further research. The possible areas of future research of this project were also suggested.